2020
DOI: 10.1109/ojcoms.2020.2999104
|View full text |Cite
|
Sign up to set email alerts
|

Channel Characterization and Modeling for Optical Wireless Body-Area Networks

Abstract: We address channel characterization and modeling for medical wireless body-area networks (WBANs) based on the optical wireless technology. We focus on the intra-WBAN communication links, i.e., between a set of medical sensors and a coordination node, placed on the patient's body. We consider a realistic mobility model, e.g., inside a hospital room, which takes into account the effect of shadowing due to body parts movements and the variations of the underlying channels. To take into account the global and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Another advantage of the OWC is the absence of small-scale fading associated with multipath. A comparative study of the specificities of the optical channel compared to the radio channel was reported in [ 22 ]. It highlighted high sensitivity to blocking effects due to the body and a slowly varying behavior of the channel with a relatively long coherence time compared to RF links.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of the OWC is the absence of small-scale fading associated with multipath. A comparative study of the specificities of the optical channel compared to the radio channel was reported in [ 22 ]. It highlighted high sensitivity to blocking effects due to the body and a slowly varying behavior of the channel with a relatively long coherence time compared to RF links.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the communication model may be affected due to the variations of the user body sizes, shape, skin texture, and flexibility. Features associated with the subject determines the quality of the signal communication [17,21]. In a very dynamic environment of a signal carrier, such as WBAN application, network designers must consider several normalized features when proposing a transmission model.…”
Section: Wban Channel Modelmentioning
confidence: 99%
“…[ 9 , 24 , 25 ] discussed the use of VLC in multi-user environments. Recently, the authors in [ 26 ] characterized the intra-OBAN channels by considering the effects of mobility and shadowing that occurred as a result of body parts and realistic body movements. In another study [ 27 ], the authors have reported the effects of several parameters, e.g., source directivity, transmitted optical power, position of on-body sensors, and the number of PDs that were installed on the ceiling.…”
Section: Related Workmentioning
confidence: 99%